Effect of Different Ecbolic Therapy on Serum Macro-Micro Minerals Profile in Dystocia Affected Dangi Cows - Bhoi, D.B.; Khasatiya, C.T.; Desai , V. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was conducted in eighteen dystocia affected Dangi cows that were handled without any complications from various villages of Dangs district in South Gujarat to evaluate the effect of different ecbolic therapies on serum macro-micro minerals profile. The cows were divided in to three groups consisting six cows in each. Group-I (T1) and II (T2) cows were given methylergometrine (Nexbolic, 5 mg) and dinoprost tromethamine (Lutalyse, 25 mg) i/m, respectively, soon after parturition. The cows in Group-III (T3) received herbal ecbolic (Exapar, 2-4 boluses, b.i.d.) for first 10 days postpartum. The jugular blood samples were collected aseptically on day 0 (day of calving), 7th, 14th 21st and 28th day postpartum to harvest serum. The serum macro-minerals (calcium, inorganic phosphorus, magnesium) and micro-minerals (copper, cobalt, zinc, iron, manganese) were analyzed using commercially available kits. The mean serum calcium level of Dangi cows did not differ significantly (p>0.05) between T1, T2 and T3. The serum calcium levels showed increasing trend from day 0 to 28th day postpartum and significantly higher (p0.05) at 0 day, 7th, 14th, 21st and 28th day postpartum within and between all the treatment groups including overall mean at different time intervals. The mean copper, cobalt, zinc, iron and manganese concentrations in treatment T1, T2 and T3 groups did not differ significantly (p>0.05) at different time intervals among all the treatment groups.
Keywords: Dangi cow; Ecbolic; Macro micro minerals; Postpartum period; Dystocia